2016
DOI: 10.1002/aenm.201670089
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Batteries: Computational Design and Preparation of Cation‐Disordered Oxides for High‐Energy‐Density Li‐Ion Batteries (Adv. Energy Mater. 15/2016)

Abstract: In article number 1600488, Gerbrand Ceder and co-workers present a computational highthroughput approach to identify novel disordered oxides for high-capacity Li-ion battery cathodes. The image shows the structures of ordered and cation-disordered Li transition metal (TM) oxides. Various TM combinations, predicted to form either ordered or disordered phases are visualized as small and large circles, respectively. LITHIUM BATTERIES

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…2b). 68 Monte-Carlo Percolation Simulations was proposed by Lee's group 52 to reveal the fact that cation disordered structure with Liexcess results into the formation of 0-TM percolation channels for Lithium ions diffusion. Contrasting with the layered cathodes that usually suffer from interlayer stacking issues, Li/Ni cationic mixing, particle cracking or even structural collapse in lithium ions deintercalation process under high voltage condition, DRXs compounds are quite more stable, because random cation distribution can suppress volume changes and remedy problems related to structural degradation during charge and discharge.…”
Section: Composition and Structurementioning
confidence: 99%
“…2b). 68 Monte-Carlo Percolation Simulations was proposed by Lee's group 52 to reveal the fact that cation disordered structure with Liexcess results into the formation of 0-TM percolation channels for Lithium ions diffusion. Contrasting with the layered cathodes that usually suffer from interlayer stacking issues, Li/Ni cationic mixing, particle cracking or even structural collapse in lithium ions deintercalation process under high voltage condition, DRXs compounds are quite more stable, because random cation distribution can suppress volume changes and remedy problems related to structural degradation during charge and discharge.…”
Section: Composition and Structurementioning
confidence: 99%
“…Until recently, cation disorder between Li and transition metal (TM) sites was considered detrimental to battery performance. Although this has been proven true in some cases, experimental and theoretical studies [11] conducted by Ceder et al [12,13] have indicated that Li and TM crystallized in a disordered rock salt (DRX) lattice have the potential to reversibly store Li by exploiting the Li percolation network. [13] The discovery of the percolation network has opened up the material space for cathodes, allowing the use of various transition metal redox chemistries for charge compensation during (de)lithiation, for example, Mn 3þ =Mn 4þ , [14,15] Mn 2þ =Mn 4þ , [13,16] Cr 3þ =Cr 5þ , [17] Mo 3þ =Mo 6þ , [18] and V 3þ =V 5þ .…”
Section: Introductionmentioning
confidence: 99%